1978
DOI: 10.1139/z78-079
|View full text |Cite
|
Sign up to set email alerts
|

Underwater acoustic signals of the narwhal (Monodon monoceros)

Abstract: Underwater sound recordings of the narwhal from northern Baffin Island are analyzed and described. Frequency ranges of pulsed and pure tone vocalizations are found to be somewhat greater than previously observed. An earlier report that narwhals generate exclusively narrowband sounds is confirmed. Narwhal pulses appear to have a potential function as both orientation and communication signals. Pulse series having irregular repetition rates resemble the echolocation clicks of captive delphinids, and it is sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 4 publications
7
55
0
2
Order By: Relevance
“…The pulsatile component of the combined tonal/pulsed signals quantified here was characterized by a higher upper frequency limit ͑up to 48 kHz͒ compared to earlier recordings. Previous studies ͑Watkins et al, 1971;Ford and Fisher, 1978͒ reported observing tonal signals with properties that were both similar to and different from the whistles analyzed here. The frequency ranges overlapped but the whistles that were recorded here had higher harmonics, extending the upper bound of these tonal vocalizations to at least 48 kHz.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The pulsatile component of the combined tonal/pulsed signals quantified here was characterized by a higher upper frequency limit ͑up to 48 kHz͒ compared to earlier recordings. Previous studies ͑Watkins et al, 1971;Ford and Fisher, 1978͒ reported observing tonal signals with properties that were both similar to and different from the whistles analyzed here. The frequency ranges overlapped but the whistles that were recorded here had higher harmonics, extending the upper bound of these tonal vocalizations to at least 48 kHz.…”
Section: Discussionsupporting
confidence: 54%
“…In this manuscript, these signals will be referred to as combined tonal/pulsed signals. Finally, narrow-band, frequency modulated ͑FM͒ whistles have been described that generally last Ͻ1.0 s ͑range: 0.1-6.0 s͒ and have a frequency range between 300 Hz and 18 kHz ͑Ford and Fisher, 1978;Møhl et al, 1990͒. Although Ford and Fisher ͑1978͒ did not find any evidence for signature content among whistles, they speculated that the different pulsed tones in their recordings were produced by separate individuals as signature calls in a social context. They recorded series of the same tone growing louder and then softer, concluding that this resulted from one individual producing each series as it approached and then swam past a stationary hydrophone.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no studies have systematically discriminated between calls of these species. Their repertoires have been explored independently, often focusing on tonal calls (Ford and Fisher, 1978;Belikov and Bel'kovich, 2006). While such information is useful, narwhals and especially beluga whales have large vocal repertoires that are only partially described, resulting in potential interspecies overlap of calls and low reliability of identification (Sjare and Smith, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…However, nondelphinid toothed whale species like the Chinese river dolphin Lipotes vexillifer ͑Jing et al 1981;Xianying et al 1981;Wang et al 1989;Wang et al 2006͒, the beaked whales of the genus Berardius spp ͑Dawson et al. 1998, Rogers andBrown 1999͒, the narwhal Monodon monocerus, and the beluga Delphinapterus leucas ͑e.g., Bel'kovich 2001, 2003;Ford and Fisher 1978;Karlsen et al 2002;Shapiro 2006;Sjare and Smith 1986;Watkins et al 1970͒ are known to produce whistles as well in a variety of contexts.…”
Section: Introductionmentioning
confidence: 99%